An awareness of building’s owner to maintain the heritage shophouses at Ipoh, Perak / Nur Amanina Azemi - Azemi, Nur Amanina (2016)
Heritage shop houses can be seen on its architectural fabric. Heritage shop houses can be as a landmark for the some cities in the world. Mostly shop houses are double-storey. For the first floor the structure are being made from the timber and for the ground floor the structure are from brick. Perak is one of the states that have a lot of heritage shop houses that are already being gazette by local authority. The aim of this study is to investigate an awareness of building’s owner to maintain the heritage shop houses. The objectives of this study are to study about the architectural style for heritage shop houses, to identity the current condition of shop houses facade and also to know an awareness of building’s owner to maintain the heritage shop houses facade. Methodology that applied in this study is quantitative method by distribute the questionnaire survey to the selected lane that have gazette shop houses at Ipoh, Perak area. For the recommendation procedure to know an awareness of building’s owner to maintain heritage shop house using the observation based on the data that get from the questionnaire.